(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2026)
Stable demographic development and the balanced territorial distribution of labor resources are important factors for economic growth and social stability. This study analyzes the interrelationship between demographic processes—such as fertility, mortality, and migration—and the distribution of labor resources. The aim of the research is to identify the factors behind regional labor market imbalances and to develop policy recommendations to mitigate them. Based on statistical and comparative analyses, the findings reveal that uneven demographic development, internal migration, and disparities in economic opportunities are the main sources of labor resource imbalances. The study also highlights the role of human capital, regional policy, and institutional mechanisms in reducing these challenges. The results indicate that achieving a balanced labor market requires coordinated measures in demographic policy, education, and employment, as well as the development of regional infrastructure and the creation of jobs.